Spraying of swine buildings with lemon grass (Cymbopogon citratus) essential oil does not produce blood absorption in swine - Seung-Jin Lee; Ki-Hyun Kim; Abraham Fikru Mechesso; Na-Hye Park; Seung-Chun Park (International Journal of Phytomedicine, 2016)
Cymbopogon citratus (Lemon grass) essential oils have been used in swine buildings to reduce the offensive odor emanating from swine buildings. The present study was designed to investigate plasma residues of citral which is a major constituent of the essential oils of Cymbopogon citratus. An HPLC method was established, validated and used for the determination of citral in swine plasma harvested from blood samples taken at the 14th, 21st and 28th day after spraying swine buildings with the 3% Lemon grass essential oil. Thereafter, analysis of the sample was conducted using HP ODS Hypersil column (200 × 4.6 mm, 5 µm) with a mobile phase consisting of methanol and 0.5% acetic acid; and a flow rate of 1mL/ min. The method was validated for parameters such as accuracy, precision, linearity and detection limits. Plasma spiked with standard citral (95%) revealed two chromatograms with retention times of about 10.7 and 12.2 minutes. The calibration curves for the citral isomers were found to be linear in the tested concentration ranges and mean recoveries wre 101% and 99.17%. This method was used to determine the residues of citral in swine plasma pretreated with methanol. Surprisingly, there was no any detectable level of citral in swine plasma within the 28 days of exposure. spraying of swine buildings with essential oils of lemon grass oil does not cause plasma residues of citral.